The III–V Triple-Junction Solar Cell Characteristics and Optimization with a Fresnel Lens Concentrator - Yin Guo; Qibing Liang; Bifen Shu; Jing Wang; Qingchuan Yang (International Journal of Photoenergy)
At present, the Fresnel lens are commonly used as the condenser in high-concentrating photovoltaic (HCPV) modules. It is ideally believed that the output power of a III–V triple-junction solar cell which is placed on the focal plane of a Fresnel lens is the largest, because the intensity of the sunlight on the focal plane is the largest. Actually, according to our work, the dispersion of sunlight through a Fresnel lens and the nonparallelism and divergence of the incident light will lead to changes in the spectrum and the homogeneity of illumination, and cause a drop of the solar cell output. In this paper, the influence of the dispersion and nonparallel incidence of the light on the output of a triple-junction solar cell at different positions near the focal plane were theoretically studied, combined with the light-tracing simulation method and triple-junction solar cell circuit network model. The results show that the III–V triple-junction solar cell has the highest output power in both sides of the focal plane positions. The output power can be increased by about 15% after being optimized. The simulation results were verified by the experiments.